Modeling interbank relations during the international financial crisis - Savva, Christos S. (My University, 2011)
This paper examines the effects of the current financial crisis on the correlations of four international banking stocks. We find that in the beginning of the crisis banks generally show a transition to a higher correlation followed by a dramatic decline towards the end of 2008. These findings are consistent with both traditional contagion theory and the more recent network theory of contagion.
Keywords: Financial Crises; Contagion; Interbank Markets; Financial Crises; Contagion; Interbank Markets